A SYSTEMATIC REVIEW: MOBILE APPLICATION MONITORING POST OPERATION CAESAREAN SECTION - zahrotul - widad; Ninuk Dian Kurniawati; Kristiawati Kristiawati (Placentum)
Introduction: Surgical wound infection (ILO) is a serious complication and can cause significant morbidity, including increasing the risk of readmission and prolonging recovery time.